Evolutionary biology and the question of teleology. (August 2016) - Ruse, Michael
Abstract: Teleology—what Aristotle called "final cause"—is trying to understand things in terms of the future, as when we ask about the plates on the back of the dinosaur, stegosaurus, and suggest that they might sometime be used to control the internal temperature of the brute. Recently the philosopher Thomas Nagel has argued for a wholesale embrace of teleological thinking in the sciences, particularly the life sciences. I argue that Nagel's thinking is shoddy and ill-informed, but that in some sense biologists do (with reason) seem drawn to teleological understanding, and so the correct response is not outright rejection of the very idea but a more informed and sympathetic approach to those aspects of nature that seem to call for final cause thinking.